Crystal structure of 1-methanesulfonyl-1,2,3,4-tetrahydroquinoline - Jeyaseelan, S. (Acta Crystallogr E Crystallogr Commun, 2015)
In the title compound, C(10)H(13)NO(2)S, the heterocyclic ring adopts a half-chair conformation and the bond-angle sum at the N atom is 347.9°. In the crystal, inversion dimers linked by pairs of C—H⋯O hydrogen bonds generate R (2) (2)(8) loops.